2021
DOI: 10.21037/atm-21-367
|View full text |Cite
|
Sign up to set email alerts
|

Functional plasticity abnormalities over the lifespan of first-episode patients with major depressive disorder: a resting state fMRI study

Abstract: Background: Neurodevelopmental and neurodegenerative theories of depression suggest that patients with major depressive disorder (MDD) may follow abnormal developmental, maturational, and aging processes.However, a lack of lifespan studies has precluded verification of these theories. Herein, we analyzed functional magnetic resonance imaging (fMRI) data to comprehensively characterize age-related functional trajectories, as measured by the fractional amplitude of low frequency fluctuations (fALFF), over the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Two studies investigated the abnormal connection patterns between MDD patients and patients with amnestic mild cognitive impairment disease or Parkinson’s disease, which lacked results compared with normal controls ( Liang et al, 2016 , Zheng et al, 2017 ). The study of Yang et al only reported the connectivities that had changed but did not indicate whether the changes were enhanced or weakened ( Yang et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies investigated the abnormal connection patterns between MDD patients and patients with amnestic mild cognitive impairment disease or Parkinson’s disease, which lacked results compared with normal controls ( Liang et al, 2016 , Zheng et al, 2017 ). The study of Yang et al only reported the connectivities that had changed but did not indicate whether the changes were enhanced or weakened ( Yang et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the GC approach has been widely used to investigate the intrinsic effective connectivity (EC) network in resting-state functional magnetic resonance imaging (rs-fMRI) data ( Bi et al, 2019 , Iwabuchi et al, 2017 , Jiang et al, 2017 ). The alteration of EC networks in MDD patients is viewed as an important aspect of pathogenesis and potential intervention targets of MDD ( Feng et al, 2016 , Hamilton et al, 2011 , Yang et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Granger causality analysis (GCA) is a method used for identifying the effective connectivity of the directed functional interactions from time-series data, and it has been widely used in resting-state fMRI studies ( Berlim et al, 2014 ; Gaynes et al, 2014 ; Yang et al, 2021 ). Feng et al (2016) analyzed the data of 23 drug-naive patients with first-onset MDD using GCA.…”
Section: Introductionmentioning
confidence: 99%